Efficiency Strategy to Maintain Sustainable Banking Profitability Growth Through Savings and Current Account Management - Amirudin, Ivan; Mani, Andra Ruyus; Pratama, Galih Satyawan Yudha; Raharja, Surya; Harto, Puji (LifeSciFi, 2024)
Banking performance has gone through various phases with different challenges, namely before the COVID-19 pandemic, during the pandemic, and post-pandemic. This study specifically describes the condition of banking in Indonesia with a focus on the dynamic movement of deposits and their impact on banking profits at each phase. During the post-pandemic phase, people tend to shift their funds to deposit products, seeking higher returns by taking advantage of the increase in the BI rate. This phenomenon requires banks to develop effective strategies in managing interest costs in order to maintain sustainable profit growth. The research method used is descriptive qualitative, with data collection through in-depth interviews and documentation from one of the banks in Indonesia. The research findings show that a successful deposit strategy must focus on managing low-cost funds. With this strategy, banks can maintain and even increase profit growth amidst changing market dynamics, ensuring financial sustainability in the context of economic changes and evolving monetary policies